2018
DOI: 10.3389/fmicb.2018.01393
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of Cyanobacteria in an Oligotrophic Tropical Estuary, South Atlantic

Abstract: This study assessed the species composition, distribution, and functional profiles of cyanobacteria in Camamu Bay, a tropical oligotrophic estuarine system on the northeast coast of Brazil, using shotgun metagenomic sequencing. Surface-water samples were evaluated in two different rainfall periods (rainy and dry seasons), at nine stations in the three hydrodynamic regions of the bay. At a fixed sampling station, on each season, samples were taken over a tidal cycle at 3-h intervals over 12 h. A total of 219 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 115 publications
(137 reference statements)
5
7
0
Order By: Relevance
“…The data of the present study revealed a phytoplankton community that is characteristic of a preserved tropical oligotrophic estuarine system, corroborating the oligotrophic condition of the bay (Affe, Menezes, et al, ; Affe, Rigonato, Nunes, & Menezes, ). The low variation in abiotic conditions between the dry and rainy seasons supports a stable community with ecological strategies that allow it to persist in a turbulent, non‐stratified water column (Amorim, Cirano, Soares, & Lentini, ; Amorim et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The data of the present study revealed a phytoplankton community that is characteristic of a preserved tropical oligotrophic estuarine system, corroborating the oligotrophic condition of the bay (Affe, Menezes, et al, ; Affe, Rigonato, Nunes, & Menezes, ). The low variation in abiotic conditions between the dry and rainy seasons supports a stable community with ecological strategies that allow it to persist in a turbulent, non‐stratified water column (Amorim, Cirano, Soares, & Lentini, ; Amorim et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…The data of the present study revealed a phytoplankton community that is characteristic of a preserved tropical oligotrophic estuarine system, corroborating the oligotrophic condition of the bay Affe, Rigonato, Nunes, & Menezes, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The Spirulina genus is hardly studied in Brazil, with most patents worked with it due to the fact that its species are well known and widely studied worldwide. Other species like Nostoc and Synechococcus are often chosen for studies because they are almost always found when collections are carried out and also because their genomes have already been identified worldwide, which improves understanding in the research carried out by groups in Brazil [ 9 , 54 ].…”
Section: Microalgae and Cyanobacteria As Metabolite Producersmentioning
confidence: 99%
“…In the search for inputs, it is well known that the marine environment is abundant in organisms that produce substances with high biotechnological value; enable a wide variety of products and which can be used as possible solutions to diseases due to the discovery of new substances with biological activity. Therefore, there is a great demand for different species of marine cyanobacteria and microalgae which may have unknown substances or untapped actions with pharmacological potential [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%